2020
DOI: 10.3390/microorganisms9010028
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Capability of Yeasts Isolated from Colombian Fermented Cocoa Beans to Form and Degrade Biogenic Amines in a Lab-Scale Model System for Cocoa Fermentation

Abstract: Yeast starters for cocoa fermentation are usually tested according to their enzymatic activities in terms of mucilage degradation and flavor improvement, disregarding their influence on the production or elimination of toxic compounds as biogenic amines (BAs), important for human health. In this work, we tested 145 strains belonging to 12 different yeast species and isolated from the Colombian fermented cocoa beans (CB) for their capability of producing BAs in vitro. Sixty-five strains were able to decarboxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
2
12
0
1
Order By: Relevance
“…Conversely, the citric acid content of LRFCJ samples showed an increase after fermentation, which has also been reported with fermentation of carrot juice ( Landete et al, 2013 ). The increase of the citric acid content in the LRFCJ samples may be ascribed to the hydrolytic activity of the microorganism, which can induce the higher release of citric acid from sweet cherry juice ( Delgado-Ospina et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the citric acid content of LRFCJ samples showed an increase after fermentation, which has also been reported with fermentation of carrot juice ( Landete et al, 2013 ). The increase of the citric acid content in the LRFCJ samples may be ascribed to the hydrolytic activity of the microorganism, which can induce the higher release of citric acid from sweet cherry juice ( Delgado-Ospina et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have evaluated the use of starter cultures for fine-flavor coca bean fermentation, including the use of Candida parapsilosis , Torulaspora delbrueckii and Pichia kluyveri in Scavina cacao from Brazil [ 22 ], as well as the inoculation of Pichia kudriavzevii and Saccharomyces cerevisiae in Criollo cacao from Colombia [ 23 ]. The results obtained in both studies showed the capability of yeast-based starter cultures to improve the quality of fine-flavor cacao.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, temperature can also affect the accumulation of BAs during fermentation. Delgado-Ospina et al [31] demonstrated that temperature helped to simulate the off and on of the amine metabolism during cocoa fermentation, thus regulating BA accumulation and reduction. Recently, microbial fermentation as a means to improve the safety and quality of fermented food has been widely used.…”
Section: Discussionmentioning
confidence: 99%